2016
DOI: 10.1002/ece3.2252
|View full text |Cite
|
Sign up to set email alerts
|

Specialist pollinators deplete pollen in the spring ephemeral wildflower Claytonia virginica

Abstract: Pollinators that collect pollen – and specifically, pollen‐specialist bees – are often considered to be the best pollinators of a (host) plant. Although pollen collectors and pollen specialists often benefit host plants, especially in the pollen that they deliver (their pollination “effectiveness”), they can also exact substantial costs because they are motivated to collect as much pollen as possible, reducing the proportion of pollen removed that is subsequently delivered to stigmas (their pollination “effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Similarly, trait variation within species may stabilize population density over time (Bolnick et al 2011). Often, when a high-quality pollinator is unavailable, plants benefit from visits by low-quality pollinators (e.g., Thomson 2003, Parker et al 2016, meaning that retaining the capacity to interact with both highand low-quality pollinators can produce more consistent pollination. In the Albrecht et al (2012) pollinator study, temporal niche complementarity of pollinators may also have increased plant seed set.…”
Section: The Cumulative Benefits Of Multiple Partnersmentioning
confidence: 99%
“…Similarly, trait variation within species may stabilize population density over time (Bolnick et al 2011). Often, when a high-quality pollinator is unavailable, plants benefit from visits by low-quality pollinators (e.g., Thomson 2003, Parker et al 2016, meaning that retaining the capacity to interact with both highand low-quality pollinators can produce more consistent pollination. In the Albrecht et al (2012) pollinator study, temporal niche complementarity of pollinators may also have increased plant seed set.…”
Section: The Cumulative Benefits Of Multiple Partnersmentioning
confidence: 99%
“…() demonstrated that A. erigeniae remove more pollen (61% per single visit) than B. major (23.7%) in this system (Parker et al. ), and simulation models have demonstrated that these empirical removal rates by A. erigeniae would deplete pollen faster than B. major (Parker ). In fact, simple bookkeeping shows that if a male‐phase C. virginica flower containing 2764 pollen grains (the mean pollen production, as measured by Parker et al.…”
Section: Discussionmentioning
confidence: 93%
“…Parker et al. () demonstrated that A. erigeniae remove more pollen (61% per single visit) than B. major (23.7%) in this system (Parker et al. ), and simulation models have demonstrated that these empirical removal rates by A. erigeniae would deplete pollen faster than B. major (Parker ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…, Sahli and Conner , Parker et al. ), the observed site‐ and class‐specific pollinator preferences could lead to selection on pollen color. If pollinator preferences do lead to selection, among‐site variation in pollinator preferences could maintain local pollen color variation via migration–selection balance.…”
Section: Discussionmentioning
confidence: 99%